Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China - Hjalmarsson, Anna E. (Zootaxa, 2019)
Three new species of the genus Himalopsyche (Trichoptera, Rhyacophilidae) from the Hengduan Mountains in China are described. Species delimitation was based on diagnostic features of genitalia, as well as molecular data from six genes analysed using the multi-species coalescent method STACEY. Formal descriptions are focused on genital morphology. Males of Himalopsyche viteceki sp. nov. are most similar to those of H. alticola and H. martynovi, and females are most similar to those of H. tibetana and H. velata. Himalopsyche immodesta sp. nov. is described based on a single male specimen and it most resembles the males of H. viteceki. Males of H. velata sp. nov. are most similar to H. tibetana, and females are most similar to those of H. maxima and H. tibetana. Diagnostic characters are found on segment IX and the superior and inferior appendages of male genitalia, and most notably on segment VIII in female genitalia. The newly discovered species underline the Hengduan Mountains as a potential source of yet undiscovered aquatic biodiversity.